2022
DOI: 10.1111/1541-4337.12969
|View full text |Cite
|
Sign up to set email alerts
|

Depuration of live oysters to reduce Vibrio parahaemolyticus and Vibrio vulnificus: A review of ecology and processing parameters

Abstract: Consumption of raw oysters, whether wild-caught or aquacultured, may increase health risks for humans. Vibrio vulnificus and Vibrio parahaemolyticus are two potentially pathogenic bacteria that can be concentrated in oysters during filter feeding. As Vibrio abundance increases in coastal waters worldwide, ingesting raw oysters contaminated with V. vulnificus and V. parahaemolyticus can possibly result in human illness and death in susceptible individuals. Depuration is a postharvest processing method that main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 218 publications
1
10
0
Order By: Relevance
“…(2009), our results showed that a storage phase in filtered seawater (TC, C, and B treatments) results in cleaner oysters. Moreover, consistent with other similar studies, our system improved the product safety through complete elimination of E. coli (Bernard, 1989; Campbell et al., 2022). Conversely, the treatments in which the oysters did not undergo the depuration phase in filtered seawater (treatment A and SC) had the highest percentage of samples with a slight presence of mud in suspension and the E. coli concentration remained almost the same.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(2009), our results showed that a storage phase in filtered seawater (TC, C, and B treatments) results in cleaner oysters. Moreover, consistent with other similar studies, our system improved the product safety through complete elimination of E. coli (Bernard, 1989; Campbell et al., 2022). Conversely, the treatments in which the oysters did not undergo the depuration phase in filtered seawater (treatment A and SC) had the highest percentage of samples with a slight presence of mud in suspension and the E. coli concentration remained almost the same.…”
Section: Discussionsupporting
confidence: 90%
“…Among the different existing postharvest processing for seafood preservation, short storage in land‐based tanks working in recirculating water system is a method that offers the ability to maintain oyster viability, freshness, and microbiological safety in a controlled environment, whereas they filter clean salt water that either continuously flows through a holding tank or is recirculated and replenished periodically (Lee et al., 2008). In most depuration systems, out flow water typically undergoes disinfection treatment before returning to the depuration tank through physical (UV irradiation) and/or chemical (chlorine and/or ozone) treatments to eliminate bacteria and other pathogens and spoilage microorganisms (Campbell et al., 2022; López Hernández et al., 2018). However, despite the advantages offered by this type of system, the depuration process up until now has only ever been deeply discussed and studied for shellfish coming from classified waters, according to the extent of microbial fecal contamination as zones B and C (Regulation (CE) 853/2004).…”
Section: Introductionmentioning
confidence: 99%
“…The biodeposit PPM communities (Figure 5, Table S6) also appeared quite different overall from those commonly reported in C. virginica gut and muscle tissue [196][197][198], which may be more difficult for the oysters to excrete [199]. Hence, it is likely that recommended depuration methods [200,201] could be used to help purge harvested oysters of the microbes detected in this study, thereby reducing the human health risks associated with oyster consumption in the IRL.…”
Section: Discussionmentioning
confidence: 65%
“…It consists of keeping them in germ-free water so that they "purge" the pathogenic bacteria. Key process parameters include time, temperature, salinity and current intensity (Campbell et al, 2022). Purification of V. cholerae has a limited effect when performed at room temperature (Eyles and Davey, 1984).…”
Section: Purification Of Molluscsmentioning
confidence: 99%